2009
DOI: 10.1016/j.immuni.2009.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Coactivation of Syk Kinase and MyD88 Adaptor Protein Pathways by Bacteria Promotes Regulatory Properties of Neutrophils

Abstract: Neutrophils are one of the first lines of defense against microbial pathogens and are rapidly recruited at the infection site upon inflammatory conditions. We show here that after bacterial stimulation, and in contrast to monocytes and macrophages, murine neutrophils contributed poorly to inflammatory responses; however, they secreted high amounts of the anti-inflammatory cytokine IL-10 in a DAP12 adaptor-Syk kinase and MyD88 adaptor-dependent manner. Cotriggering of TLR-MyD88- and C-type lectin receptor (CLR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
259
3
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(305 citation statements)
references
References 47 publications
38
259
3
3
Order By: Relevance
“…12), were found to express IL-6 mRNA and to produce IL-6 when cultured for 14 h in vitro with 25 mM R848 or 10 mg ml À 1 LPS. By contrast, no IL-6 was measured in supernatants from bone marrow-derived neutrophils cultured under the same conditions, confirming previous findings 42 . In line with these results, only inflammatory peritoneal, but not bone marrow, neutrophils were found to express TLR7 and TLR8 mRNA (Fig.…”
Section: Il-6 Production By Murine Neutrophils In Vitro and In Vivosupporting
confidence: 90%
“…12), were found to express IL-6 mRNA and to produce IL-6 when cultured for 14 h in vitro with 25 mM R848 or 10 mg ml À 1 LPS. By contrast, no IL-6 was measured in supernatants from bone marrow-derived neutrophils cultured under the same conditions, confirming previous findings 42 . In line with these results, only inflammatory peritoneal, but not bone marrow, neutrophils were found to express TLR7 and TLR8 mRNA (Fig.…”
Section: Il-6 Production By Murine Neutrophils In Vitro and In Vivosupporting
confidence: 90%
“…These findings suggest that NKT cells regulate IL-1β production during CLP-induced sepsis in an IFN-γ-independent manner. Several studies prior to ours demonstrated that neutrophils produce IL-10 in response to bacterial infection in a DAP12 adaptor-Syk kinase and MyD88-dependent manner [36], and constitute a major cell subset for producing IL-10 during sepsis [37,38]. Consistent with these findings, our experiments demonstrated that neutrophil deletion in WT mice decreases IL-10 and C5a levels in serum and peritoneal fluid compared with CD1d −/− mice during CLP-induced sepsis.…”
supporting
confidence: 90%
“…Murine neutrophils, which flood into the peritoneal cavity in large numbers, are a rich source of 20) although other cell types may well also contribute to the production of this cytokine (23,24). In this early period, when the IL-10 concentration in the peritoneum is high, the macrophages formed are of the MHC II lo type, whereas later, when the IL-10 concentration has fallen, the macrophages formed are of the MHC II hi type.…”
Section: Discussionmentioning
confidence: 99%